One minute out - Greaney, Mark (Greaney, Mark. Gray Man novel, 2020)
"Is it ever the wrong time to do the right thing? That's the question the Gray Man faces in the latest explosive novel from New York Times bestselling author Mark Greaney. I am Court Gentry. In my time, I've seen plenty of bad stuff. Some things worse than others, but nothing that can match this horror show. I was on a simple mission in Bosnia. A bad guy needed to be put down; in and out, no problem. But then I stumbled across a nightmare-a room full of women and children who were being trafficked to rich scum. Since then, I've been tracking their smuggling ring around the globe, and I'm finally near the top. I've got the sociopathic ringleaders in my sights, ready for a takedown, but my CIA handlers have different plans for me. Now I've got to make a decision: duty or honor. They all think they have me boxed in, but there's one thing they're forgetting: I am the Gray Man"--